Simultaneous Realization of Good Piezoelectric and Strain Temperature Stability via the Synergic Contribution from Multilayer Design and Rare Earth Doping. (25th December 2022) - Zhang, Yumin; Yu, Yungang; Zhang, Nan; Zheng, Ting; Wu, Jiagang
Abstract: Niobate‐based lead‐free piezoceramics have attracted wide attention due to their excellent piezoelectric properties. Although the temperature sensitivity of piezoelectricity or strain in one sample has been solved to a certain extent, how to simultaneously improve the temperature stability of both in one sample is still an issue. Herein, by constructing multilayer composite ceramics and doping Ho element, both improved piezoelectric and strain temperature stability (the variations are below 3% under 30–100 °C) are achieved, showing great property advantage compared with previous reports. Different from the compositionally graded composite ceramic design, the Ho doping can not only increase orthorhombic‐tetragonal phase transition temperature ( T O‐T ) and then create the condition for the formation of successive phase transition, but also stabilize the oriented domain state. Therefore, the excellent temperature stability of both piezoelectricity and strain can be attributed to the multistep phase transition induced by the multilayer design, the fine regulation of T O‐T interval by the optimization of lamination combination, and the stabilized polarization induced by Ho doping. The new strategy for solving both piezoelectric and strain temperature sensitivity can further promote the commercial application of potassium sodium niobate‐based lead‐free piezoelectric ceramics. Abstract : By constructing multilayer composite ceramics and doping Ho element, both improved piezoelectric and strain temperature stability (the variations are below 3% at 30–100 °C) are achieved, showing great property advantage compared with previous reports.